Descemet membrane endothelial keratoplasty versus descemet stripping automated endothelial keratoplasty - Tourtas, Theofilos; Laaser, Kathrin; Bachmann, Bjoern O.; Cursiefen, Claus; Kruse, Friedrich (American Journal of Ophthalmology, 2012)
To evaluate visual outcome and endothelial cell survival after Descemet membrane endothelial keratoplasty (DMEK) in comparison with Descemet stripping automated endothelial keratoplasty (DSAEK).Single-center, retrospective, consecutive case series.Thirty-eight eyes of 38 consecutive patients undergoing DMEK, who completed a 6-month follow-up, were compared with 35 eyes of 35 consecutive patients undergoing DSAEK for Fuchs endothelial dystrophy or pseudophakic bullous keratopathy. Main outcome measures included best-corrected visual acuity (in logarithm of the minimal angle of resolution [logMAR] units) and endothelial cell density within a 6-month follow-up.Best-corrected visual acuity increased from 0.70 ± 0.48 logMAR and 0.75 ± 0.32 logMAR before surgery to 0.21 ± 0.14 logMAR and 0.48 ± 0.19 logMAR 3 months after DMEK and DSAEK (P < .001), respectively, and to 0.17 ± 0.12 logMAR and 0.36 ± 0.15 logMAR 6 months after DMEK and DSAEK (P < .001), respectively. Endothelial cell density decreased from 2575 ± 260 cells/mm(2) and 2502 ± 220 cells/mm(2) before surgery to 1498 ± 244 cells/mm(2) and 1778 ± 420 cells/mm(2) 3 months after DMEK and DSAEK (P < .001), respectively, and to 1520 ± 299 cells/mm(2) and 1532 ± 495 cells/mm(2) 6 months after DMEK and DSAEK (P = .483), respectively. Central corneal thickness decreased from 652 ± 92 ?m before surgery to 517 ± 45 ?m 6 months after DMEK, and from 698 ± 137 ?m before surgery to 618 ± 66 ?m 6 months after DSAEK.DMEK provided faster and more complete visual rehabilitation when compared with DSAEK. However, there were no significant differences concerning endothelial cell survival within a 6-month follow-up.
EVALuna2:21063